2020
DOI: 10.1097/mcg.0000000000001340
|View full text |Cite
|
Sign up to set email alerts
|

Altered Expression of the Epithelial Mucin MUC1 Accompanies Endoscopic Recurrence of Postoperative Crohn’s Disease

Abstract: Background: MUC1-glycoprotein is expressed at low levels and in fully glycosylated form on epithelial cells. Inflammation causes MUC1 overexpression and hypoglycosylation. We hypothesized that overexpression of hypoglycosylated MUC1 would be found in postoperative Crohn’s disease (CD) recurrence and could be considered an additional biomarker of recurrence severity. Methods: We examined archived neo-terminal ileum biopsies from patients with prior ileoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…Moreover, we observed moderate decreases in the expression of MUC2 and MUC5AC under inflamed conditions. These findings agree with studies on IBD patients and mice with an artificially induced colitis [34,[96][97][98]. Contrasting our results, IBD has formerly been associated with higher expression levels of MUC5AC [34,98].…”
Section: Comparison Of In Vitro Modelssupporting
confidence: 92%
“…Moreover, we observed moderate decreases in the expression of MUC2 and MUC5AC under inflamed conditions. These findings agree with studies on IBD patients and mice with an artificially induced colitis [34,[96][97][98]. Contrasting our results, IBD has formerly been associated with higher expression levels of MUC5AC [34,98].…”
Section: Comparison Of In Vitro Modelssupporting
confidence: 92%
“…A total of 957 DEGs were screened: 478 up regulated genes and 479 down regulated genes. Lee et al [41], Gijsbers et al [42], Hashash et al [43], Wnorowski et al [44] and Kyodo et al [45] found that FCGR3A, CXCL8, MUC1, HCAR3 and DUOX2 might play an important role in the pathophysiology of CD. Nourse et al [46] and Nakashima et al [47] found that FCGR3A and MUC1 was altered expressed in coagulation and fibrinolysis.…”
Section: Discussionmentioning
confidence: 99%
“…Mucin-1 was a major product which secreted by goblet cells 26 and was a component of ECM 27 . Recent studies 28 32 had found that the expression of MUC1 in CD was significantly increased. This was consistent with the fact that methylation of MUC1 was reduced in this study.…”
Section: Discussionmentioning
confidence: 99%